Addressing for 6LoWPAN WBAN. (December 2016) - Wang, Xiaonan; Sun, Qi; Wang, Dong
Highlights: This paper makes a distinction between HoA and CoA, and proposes the addressing algorithms for HoA and CoA, respectively. The CoA addressing is achieved based on the HoA addressing, so the CoA addressing latency is shortened. A WBAN performs the HoA/CoA addressing algorithm as a unit, so the addressing latency is reduced. Abstract: Background and Objective: In 6LoWPAN, a node is configured with a home address (HoA) when it starts. Each time a node enters a new IP domain it is configured with a care-of address (CoA) to guarantee correct communications. That is, a node performs only one HoA configuration process but multiple CoA ones during its lifetime. Therefore, it is significant to reduce the CoA configuration latency since the CoA latency mainly determines the average addressing latency. This paper proposes an addressing scheme for 6LoWPAN in the real-time patient monitoring scenario and the main objective is to shorten the CoA addressing latency. Methods: This scheme makes a distinction between HoA and CoA, and proposes the addressing algorithms for HoA and CoA, respectively. The CoA addressing is achieved based on the HoA addressing and a wireless body area network performs the HoA/CoA addressing algorithm as a unit, so the addressing latency is reduced. Results: The CoA addressing latency is reduced because it is performed based on HoA addressing. Conclusions: Making a distinct between HoA and CoA and achieving the CoA addressing based on the HoA addressing can help reduce the addressing latency.